Improved understanding of drought controls on seasonal variation in Mediterranean forest canopy CO2 and water fluxes through combined in situ measurements and ecosystem modelling - Keenan, T.; Garcia, R.; Friend, A. D.; Zaehle, S.; Gracia, C.; Sabate, S. (BIOGEOSCIENCES, 2009)
Water stress is a defining characteristic of Mediterranean ecosystems, and is likely to become more severe in the coming decades. Simulation models are key tools for making predictions, but our current understanding of how soil moisture controls ecosystem functioning is not sufficient to adequately constrain parameterisations. Canopy-scale flux data from four forest ecosystems with Mediterranean-type climates were used in order to analyse the physiological controls on carbon and water flues through the year. Significant non-stomatal limitations on photosynthesis were detected, along with lesser changes in the conductance-assimilation relationship. New model parameterisations were derived and implemented in two contrasting modelling approaches. The effectiveness of two models, one a dynamic global vegetation model ({''}ORCHIDEE{''}), and the other a forest growth model particularly developed for Mediterranean simulations ({''}GOTILWA+{''}), was assessed and modelled canopy responses to seasonal changes in soil moisture were analysed in comparison with in situ flux measurements. In contrast to commonly held assumptions, we find that changing the ratio of conductance to assimilation under natural, seasonally-developing, soil moisture stress is not sufficient to reproduce forest canopy CO2 and water fluxes. However, accurate predictions of both CO2 and water fluxes under all soil moisture levels encountered in the field are obtained if photosynthetic capacity is assumed to vary with soil moisture. This new parameterisation has important consequences for simulated responses of carbon and water fluxes to seasonal soil moisture stress, and should greatly improve our ability to anticipate future impacts of climate changes on the functioning of ecosystems in Mediterranean-type climates.
APSAPSThe following values have no corresponding Zotero field: pub-location: BAHNHOFSALLEE 1E, GOTTINGEN, 37081, GERMANY publisher: COPERNICUS GESELLSCHAFT MBH
Keywords: ecosystem functioning; forest ecosystems; Mediterranean; water stress

Thinning effects on carbon allocation to fine roots in a Quercus ilex forest - López, B. C.; Sabate, S.; Gracia, C. A. (Tree Physiology, 2003)
The dynamics of the fine root system are relevant to calculations of the carbon balance of the ecosystem, and there is also a need to quantify changes in this component caused by disturbances. Mediterranean forest systems have historically been coppiced to obtain charcoal. As a result of the resprouting capacity of holm oaks (Quercus ilex L.), these forests present more than 50% of their biomass below ground (stump + roots > 1 cm in diameter), but the effects of thinning on the fine root system are unknown. Fine root biomass, production, mortality and longevity were studied in a control and a thinned Mediterranean holm oak forest by minirhizotron methodology. Observations of fine roots started 2 years after thinning and continued for almost 3 years. Extraction of 80% of the former basal area of the forest greatly affected carbon allocation patterns. Biomass increased by more than 100%, production increased by 76%, mortality increased by 32% and longevity decreased by around 2 weeks. The greatest differences between treatments were associated with differences in growth during autumn months in the top 40 cm of soil, particularly between 10 and 20 cm depth.
10.1093/treephys/23.17.121710.1093/treephys/23.17.1217
Keywords: biomass; longevity; mortality; production

Fine-root longevity of Quercus ilex - López, B.; Sabate, S.; Gracia, C. A. (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C. A.; Sabate, S.; Tello, E. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: climate change; mediterranean forest; Modelling